Isthmus incidence in human permanent mandibular first molars of a South Indian population: A cone-beam computerized tomographic study - Jeyaraman Venkataraman Karunakaran; Modachur Muruganathan Premkumar; Ganapathy Aarthi; Nachimuthu Jayaprakash; Swaminathan Senthil Kumar (Wolters Kluwer Medknow Publications, 2019)
Aim: This study aimed to analyze incidence of isthmus in human permanent mandibular first molar teeth using cone-beam computed tomographic imaging techniques in a South Indian population. Materials and Methods: Three hundred permanent mandibular first molar teeth were collected, cleaned, and stored in normal saline. They were divided into groups (GPs) I and II based on number of roots, and were further subdivided (right and left [RL] subgroups A and B for GP I; and RL subgroups C and D for GP-II). Samples were processed and isthmus incidence was evaluated by cone-beam tomography, compared, and statistically analyzed. Results: Overall in mandibular first molars, the isthmus incidence in mesial root was 97.2%, distal root was 39%, and distolingual root was 0%. There was no statistically significant difference between the right and left mandibular first molar teeth with regard to incidence of isthmus (P > 0.05). There was an incidence of type I (38.67%), type II (56.33%), type III (3%), and type IV (2%) isthmuses in mesial root and type I (12.33%), type II (16%), and type III (10.67%) in distal root. Conclusion: Incidence of isthmus was very high in the mesial root of the mandibular first molar and should be factored during nonsurgical and surgical endodontic treatment procedures to achieve successful treatment outcomes.